Circulando (n)a sala de aula: histórias e escolhas em torno do material didático usado pelo(a) professor(a) de língua inglesa - Izabella Leal Goncalves (2019)
In this case study, I investigate an English as a Foreign Language teacher and his stories (the experiences, representations, theories and discourse that constitute him) and try to assimilate how they relate to the learning materials he produces, selects and/or adapts. I aim to understand how the teacher uses these materials in class, what stories they comprise, and how these stories are embodied within EFL teaching and learning in a public school setting. For that purpose, I rely on theories of identity, responsible positioning, and materials production. The data were gathered by means of a non-structured interview with the investigated teacher, voice memos obtained via WhatsApp, classroom observations and a sample of the learning materials used by the teacher. This qualitative research applies principles and procedures of Discourse Analysis in order to identify and analyze the meaning effects generated by the discourse that circulates within and around the classroom environment. Results suggest that stories reveal the internal makings of the teacher, the way he sees himself and the way he positions himself in the classroom. Stories are also incorporated in the teacher's in-class decisions, including those related to material selection. These circulating stories can trigger identifications between teacher and students, which may produce shifts in student behavior. Finally, I conclude that stories may point to fruitful ways for teachers to (re)think their practices.